(untitled) (Forum for Linguistic Studies, 2024)
The development of Islamic education is measured with the purpose to compete in global competition. Bureaucracy governance becomes the most fundamental problem which has not been administered professionally. This cause is based on traditional religious beliefs that have an exclusive side about modernization. This research finds out about bureaucratic governance examination to develop the quality administration of Ma’arif Islamic Senior High School in Ambulu, Jember Regency. This madrassa is one of the religious education institutions owned by Ma’arif NU Education Institution and has succeeded to improve its quality. This study focuses on bureaucracy theories’ important elements which consist of three: governance rules, authority, and work distribution to maintain the administration quality. The purpose of this research is providing an explanation of bureaucratic governance in order to develop the school administration quality. Theses rules are aimed to develop the fragmented value and strengthen the institutional market-adhocracy function. Second, the authority governance which carried out by the customs authority model. There are two integrated models, namely rational-legal and transformative attractiveness authority. Rational legal is the basis for school legitimacy same with the government and PBNU. Meanwhile, the attractiveness transformation is implemented as the basis for the local authority that optimizes Islamic values on the school’s quality development. And the third is the work distribution governance.